WATER HOLDING CAPACITY OF PEAR LEAVES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The results of studying the waterretaining capacity of leaves of 14 pear varietiesfrom the collection of the Scientific ResearchInstitute Botanical Garden named after V.I. E.Gareeva NAS KR. Varieties with high waterretaining capacity have been selected.
Keywords: introduction, pear varieties, wilting, water-holding capacity, moisture loss, drought resistance.